Why so few? Landslides triggered by the 2002 Denali earthquake, Alaska - Gorum, Tolga; Korup, Oliver (Prof.); van Westen, Cees J.; van der Meijde, Mark; Xu, Chong; van der Meer, Freek D. (Quaternary Science Reviews, 2014)
The 2002 M-w 7.9 Denali Fault earthquake, Alaska, provides an unparalleled opportunity to investigate in quantitative detail the regional hillslope mass-wasting response to strong seismic shaking in glacierized terrain. We present the first detailed inventory of similar to 1580 coseismic slope failures, out of which some 20% occurred above large valley glaciers, based on mapping from multi-temporal remote sensing data. We find that the Denali earthquake produced at least one order of magnitude fewer landslides in a much narrower corridor along the fault ruptures than empirical predictions for an M 8 earthquake would suggest, despite the availability of sufficiently steep and dissected mountainous topography prone to frequent slope failure. In order to explore potential controls on the reduced extent of regional coseismic landsliding we compare our data with inventories that we compiled for two recent earthquakes in periglacial and formerly glaciated terrain, i.e. at Yushu, Tibet (M-w 6.9, 2010), and Aysen Fjord, Chile (2007 M-w 6.2). Fault movement during these events was, similarly to that of the Denali earthquake, dominated by strike-slip offsets along near-vertical faults. Our comparison returns very similar coseismic landslide patterns that are consistent with the idea that fault type, geometry, and dynamic rupture process rather than widespread glacier cover were among the first-order controls on regional hillslope erosional response in these earthquakes. We conclude that estimating the amount of coseismic hillslope sediment input to the sediment cascade from earthquake magnitude alone remains highly problematic, particularly if glacierized terrain is involved. (C) 2014 Elsevier Ltd. All rights reserved.